2005
DOI: 10.1002/mame.200500200
|View full text |Cite
|
Sign up to set email alerts
|

Oxypropylation of Lignins and Preparation of Rigid Polyurethane Foams from the Ensuing Polyols

Abstract: Summary: Different lignins were converted into polyols by a chain extension reaction with propylene oxide (PO). Thus, soda lignin from Alfa (Stipa tenacissima) (SL), organosolv lignin from hardwoods (OL), kraft lignin (KL) from softwood and oxidized organosolv lignin (OOL) were oxypropylated in a batch reactor at 180 °C in the presence of KOH as catalyst. The ensuing polyols were characterized by FTIR and 1H NMR spectroscopy, which showed that they had incorporated poly(propylene oxide) grafts into their struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
163
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(174 citation statements)
references
References 15 publications
6
163
0
2
Order By: Relevance
“…Several studies have suggested that the solubility and uniformity of the lignin are the key parameters that affect its reactivity as a substitute for polyol in PU fabrication (Hsu and Glasser 1976;Saraf et al 1985;Rials and Glasser 1986;Mörck et al 1988;Ciobanu et al 2004;Hatakeyama et al 2008). Lignin substitution in PU could be achieved directly by the combination with polyol (Yoshida et al 1990;Evtuguin et al 1998;Vanderlaan and Thring 1998;Cateto et al 2008) or through chemical modifications (Glasser 1989;Gandini et al 2002;Nadji et al 2005;Ahvazi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the solubility and uniformity of the lignin are the key parameters that affect its reactivity as a substitute for polyol in PU fabrication (Hsu and Glasser 1976;Saraf et al 1985;Rials and Glasser 1986;Mörck et al 1988;Ciobanu et al 2004;Hatakeyama et al 2008). Lignin substitution in PU could be achieved directly by the combination with polyol (Yoshida et al 1990;Evtuguin et al 1998;Vanderlaan and Thring 1998;Cateto et al 2008) or through chemical modifications (Glasser 1989;Gandini et al 2002;Nadji et al 2005;Ahvazi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lignin substitution in polyurethane could be achieved either by direct substitution, in combination with polyols, 10,11,15 or through chemical modification. 8,16,17 The objective of lignin modification is to increase the reactivity of specific functional groups in lignin and enhance the polycondensation process during the production of biobased polyurethanes. 16,17 For example, free phenolic ÀOH groups are found to be more reactive 18 than benzylic ÀOH except toward diisocyanates.…”
Section: ' Introductionmentioning
confidence: 99%
“…The high functionality associated to these polyols makes them ideal for the synthesis of RPU foams. Several studies revealed that RPU foams obtained from lignin based polyols present insulating properties, dimensional stability and accelerated ageing behaviour very similar to those prepared with commercial polyols [2][3]. Moreover, the intrinsic properties of lignin will also contribute to an improvement of moisture and flame resistance [4].…”
mentioning
confidence: 99%